أهمية قياس حموضة المري عند الأطفال ذوي الأمراض التنفسية الناكسة - ديب غزل; الحكيم أمل; غانم ربى (Latakia University Journal -Medical Sciences Series, 2017)
أجريت هذه الدراسة لتبيان أهمية تطبيق اختبار ال PH- Metry في تشخيص الجزر المعدي المريئي عند الأطفال ذوي الأمراض التنفسية الناكسة, ولمعرفة أكثر الأعراض السريرية الهضمية وخارج الهضمية(التنفسية) شيوعاً المرافقة للجزر المعدي المريئي المرضي في الحالات المدروسة. شملت الدراسة 30 طفلاً تراوحت أعمارهم بين شهرين و 11سنة, حيث طبِّق لهم اختبار الـ PH- Metry. كان معدَّل انتشار الجزر المعدي المريئي 83.33% بين الأطفال ذوي الأمراض التنفسية , كانت أعمار معظم الأطفال أقل من3 سنوات(63.33%), وكانت لديهم أكبر نسبة للجزر %89.4, كان السعال أكثر الأعراض الصدرية شيوعاً بنسبة 90% ,وكانت نسبة انتشار الجزر الموافقة هي %92. وجدت أعراض تنفسية ليلية عند 67%من الأطفال المشاركين في البحث, وكانت نسبة انتشار الجزر 68%بينهم. وجدت علاقة هامة إحصائياً بين الإقياءات القلسية ووجود الجزر(P=0.043) و مابين انتشار الجزر والأعراض الهضمية الليلية(P=0.009). The study aimed to demonstrate the importance of applying PH- METRY test in the diagnosis of gastroesophageal reflux disease(GERD) of children with recurrent respiratory diseases, to determine the most common digestive and other clinical symptoms(respiratory) associated with GERD in the study . Thirty children with recurrent respiratory disease aged between two months and 11 years, were included in this study whom applied pH-Metry monitoring. GERD was found in 83.33% of children with recurrent respiratory disease, most patients(63.33%) were less than 3 years with the highest ratio of GERD( 89.4%). The cough was the most common of respiratory symptoms (90%). The prevalence rate of GERD between consenting patients was( 92%) .Night respiratory symptoms were found in (67%) of children. The prevalence rate of GERD between consenting patients was(68%) . Statistically significant relationship found between regurgitated vomiting and the presence of GERD (P = 0,043),and between the night digestive symptoms and GERD(P=0.009)